Towards energy self-sufficiency and integral material recovery in waste water treatment plants: Assessment of upgrading options. (1st January 2018) - Bertanza, Giorgio; Canato, Matteo; Laera, Giuseppe
Abstract: Wastewater treatment facilities are increasingly being considered as centralized installations where various resources can be recovered from the sewage. Novel technological solutions are already available for achieving this goal. However, their application to upgrade existing plants can be far more challenging than building new dedicated plants. While the scientific literature is generally focused on testing and comparing the recovery options, this work was aimed at giving a holistic evaluation of the actual impacts of upgrading existing facilities. Commercially available systems were considered for retrofitting two plants of different size (50, 000 and 500, 000 population equivalents) and achieving either energy self-sufficiency or material recovery. Based on mass and energy balances, a detailed evaluation of technical, social, economic, and administrative aspects was carried out. Environmental aspects were also included, adopting a simplified approach. It turned out that energy self-sufficiency (external energy supply reduced down to about 10% of the total need) is not far away to be achieved, with moderate techno-economic implications, especially when the plant is already equipped with primary sedimentation and anaerobic digestion. Integral recovery of treated effluent, sludge and nitrogen can also be pursued in large facilities, while several potential criticalities arise for medium-sized plants. The adopted procedure evidenced critical aspects that are often disregarded in the decision process: this may suggest where to address efforts in evaluating real situations. Highlights: Realistic upgrading scenarios were analysed. Multicriteria evaluation approach. Robust and simple assessment procedure adopted. Most critical aspects have been highlighted. Numerical scores helps in understanding the importance of different aspects.